1976
DOI: 10.2307/1128821
|View full text |Cite
|
Sign up to set email alerts
|

Order of Information Presentation and Children's Moral Judgments

Abstract: It was hypothesized that age differences in use of intent information in children's moral judgments might be due to a recency effect in the judgments of younger children. A study was conducted to examine the effect of order of stimulus presentation on children's moral judgments. The information was presented to children, ages 4-5 and 8-9 years old, through stories with either normal information order, intent-consequence, or reversed order, consequence-intent. It was found that order has a significant impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 8 publications
3
32
0
Order By: Relevance
“…For these participants, then, this manipulation appears to have lacked effectiveness. Given the efficacy of similar changes in previous research (e.g., Bearison & Isaacs, 1975;Feldman et al, 1976;Nelson et al, 1980;Nummedal & Bass, 1976), this is surprising, and suggests that failure to understand or recall occurred even more frequently in the large majority of previous research because outcomes are usually more salient and recent than intentions. However, Gvozdic et al (2016) propose that much of children's outcomebased judgment occurs because of the related issue of failure to inhibit automatic responses to outcomes.…”
Section: Discussionmentioning
confidence: 73%
“…For these participants, then, this manipulation appears to have lacked effectiveness. Given the efficacy of similar changes in previous research (e.g., Bearison & Isaacs, 1975;Feldman et al, 1976;Nelson et al, 1980;Nummedal & Bass, 1976), this is surprising, and suggests that failure to understand or recall occurred even more frequently in the large majority of previous research because outcomes are usually more salient and recent than intentions. However, Gvozdic et al (2016) propose that much of children's outcomebased judgment occurs because of the related issue of failure to inhibit automatic responses to outcomes.…”
Section: Discussionmentioning
confidence: 73%
“…Although not common in the moral judgment domain, there is work indicating that judgments are sensitive to the order in which information is presented (Austin, Ruble, & Trabasso, 1977;Feldman et al, 1976;Petrinovich, & O'Neill, 1996;Sinnott-Armstrong, Mallon, McCoy, & Hull, 2008;Wiegmann, Okan, & Nagel, 2012). Wiegmann et al (2012) point out two types of order effects (Primacy & Recency effects; Sequential effects).…”
Section: Ordermentioning
confidence: 99%
“…Wiegmann et al (2012) point out two types of order effects (Primacy & Recency effects; Sequential effects). First, developmental studies show that the first and last items of information presented in a moral scenario lead to the most extreme moral judgments (Austin et al, 1977;Feldman et al, 1976). Second, in the adult domain work has shown that if the first scenario in a sequence of multiple scenarios involves an action that is judged to be strongly prohibited, then this leads to more severe moral judgments generalize to other moral scenarios (Petrinovich & O'Neill, 1996;Wiegmann et al, 2012).…”
Section: Ordermentioning
confidence: 99%
“…By analyzing individual children's data, Grueneich (in press) also concluded that there is a developmental increase in the use of both cues. In contrast, Parsons et al (1976) and Feldman et al (1976) concluded that even kindergartners combined motive and consequence information, and that presentation order was only one variable influencing the effect of motives on moral 257 judgments. Austin et al (1977) found no differences between 6-and 8-year-olds in either the use of motives or the effects of order of presentation.…”
mentioning
confidence: 94%
“…Requests for reprints should be sent to Colleen F. Surber, Department of Psychology, University of Wisconsin,Madison,Wisconsin S3706. of the moral dilemmas presented (Gutkin, 1972), the valence of the consequence information (Costanzo, Coie, Grumet, & Farmil, 1973), the salience of intentionality information (Bearison & Isaacs, 1975), potential justifications for one's acts (Darley, Klosson, & Zanna, 1978;Hewitt^ 1975), and the order in which motive and consequence information is,presented (Austin, Ruble, & Trabasso, 1977;Feldman, Klosson, Parsons, Rholes, & Ruble, 1976;Grueneich, in press;Nummedal & Bass, 1976;Parsons, Ruble, Chereskin, Feldman, & Rholes, 1976).…”
mentioning
confidence: 99%